A comparative pharmacokinetic and pharmacodynamic study of two novel Cuban PEGylated rHuEPO versus MIRCERA® and ior®EPOCIM - Gledys Reynaldo; Leyanis Rodríguez; Roberto Menéndez; Joaquín Solazábal; Daniel Amaro; María de los A. Becquer; Yamila Colom; Haydee Gil; Juan C. Polo; Gilberto Castañeda; Braulio Jiménez-Vélez; Jorge Duconge; et al. (GarVal Editorial Ltda., 2018)
Context: The recombinant human erythropoietin (rHuEPO) stimulates the erythropoiesis process. Because this glycoprotein has a short half-life, it needs to be administrated two to three times a week. One of the technics to solve this issue is the PEGgilation. Aims: To evaluate the pharmacokinetics (PK) and pharmacodynamics of two new branched PEGylated erythropoietins (i.e., an asymmetric 32 kDa-PEG2-rHuEPO and a symmetric 40 kDa-PEG2-rHuEPO molecule) compared to non-PEGylated ior®EPOCIM and MIRCERA®. Methods: Serum concentrations of both PEGylated and non-PEGylated erythropoietins were measured at various time points in order to determine PK parameters using non-compartmental analysis approach. The reticulocyte (%), erythrocyte count and hemoglobin levels were ascertained in order to compare the effect of these molecules after administrating a single intravenous dose (10 μg/kg) of each product in male New Zealand rabbits. Results: Both branched PEGylated erythropoietin forms exhibited half-lives that were significantly longer than ior®EPOCIM (p<0.05), but not statistically different to MIRCERA®. The mean elimination half-life increased from 4 h (ior®EPOCIM) to 131 h for the 32 kDa-PEG2-rHuEPO and 119 h for the 40 kDa-PEG2-rHuEPO. Conversely, MIRCERA® exhibits a half-life of 64 h. Both PEGylated erythropoietin products significantly enhanced the stimulating effect on reticulocytes and erythrocytes formation, as well as on hemoglobin levels, when compared to ior®EPOCIM treatment up to 42 days post-dose. Conclusions: The PEGylation strategy employed in this study is an effective method to modify the pharmacokinetics and pharmacodynamics of rHuEPO molecule achieving higher half-lives and, therefore, longer in vivo bioactivity. Both of the branched PEGylated-EPO forms tested are promising candidates for human testing.